2006
DOI: 10.1097/01.fjc.0000211734.53798.1d
|View full text |Cite
|
Sign up to set email alerts
|

Paullinia pinnata Extracts Rich in Polyphenols Promote Vascular Relaxation via Endothelium-dependent Mechanisms

Abstract: Paullinia pinnata L. (Sapindaceae) is an African tropical plant whose roots and leaves are used in traditional medicine for many purposes, especially for erectile dysfunction, but its action mechanism is unknown. P. pinnata root and leaf methanolic extracts are rich in phenolic compounds. This study shows that both extracts are highly antioxidative and induce a slight transcriptional activity of peroxisome proliferator activated receptor-alpha. They also increased and decreased endothelial nitric oxide synthas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 50 publications
1
28
0
1
Order By: Relevance
“…P. pinnata flavotannin has a cardiotonic effect on isolated frog's heart and on the heart of mammals (Broadbent, 1962). Zamble et al, (2006) have demonstrated the vasodilatory activity of P. pinnata, and then it's mechanism on the penis erection. Paullinia cupana, a very close species to P. pinnata, also called Guarana, is used in sweetened or carbonated soft drinks and energy shots, an ingredient of herbal teas or contained in capsules (Weinberg and Bealer, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. pinnata flavotannin has a cardiotonic effect on isolated frog's heart and on the heart of mammals (Broadbent, 1962). Zamble et al, (2006) have demonstrated the vasodilatory activity of P. pinnata, and then it's mechanism on the penis erection. Paullinia cupana, a very close species to P. pinnata, also called Guarana, is used in sweetened or carbonated soft drinks and energy shots, an ingredient of herbal teas or contained in capsules (Weinberg and Bealer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Paullinia cupana, a very close species to P. pinnata, also called Guarana, is used in sweetened or carbonated soft drinks and energy shots, an ingredient of herbal teas or contained in capsules (Weinberg and Bealer, 2001). It was demonstrated that P. pinnata leaves and roots extracts is rich in phenolic compounds, saponins, triterpene, catechols and cardiac tannins (Bowden, 1965;Zamble et al, 2006;N'Guessan et al, 2011;Abourashed et al, 1999;Dongo et al, 2009) Adinortey et al, (2012) have studied the toxicity of the ethanolic roots of P. pinnata.…”
Section: Introductionmentioning
confidence: 99%
“…It has pinnate compound leaves hence the specific name 'Pinnata' with five serrated leaflets (Annan et al, 2013). The plant is popularly used in Nigeria and Ghana in the treatment of ailments like sore throat, leprosy liver dysfunction, snake bites, nausea and vomiting (Gill, 1992;Zamble et al, 2006;Jimoh et al, 2007;Nagori et al, 2010;Fred-Jaiyesimi et al, 2011). Previous phytochemical investigation carried out by Yusuff et al (2014) reported the presence of steroids, triterpenes, alkaloids, saponins, tannins, anthraquinones and flavonoids in the methanol extract.…”
Section: Serum Preparation and Excision Of The Livermentioning
confidence: 99%
“…Previous phytochemical investigation carried out by Yusuff et al (2014) reported the presence of steroids, triterpenes, alkaloids, saponins, tannins, anthraquinones and flavonoids in the methanol extract. Apart from the fact that P. pinnata has been proven pharmacologically to be a good anticancer plant (Tamokou et al, 2013), its methanolic extract has been reported to promote vascular relaxation through its capacity to attenuate nitric oxide oxidation and lipid peroxidation (Zamble et al, 2006).…”
Section: Serum Preparation and Excision Of The Livermentioning
confidence: 99%
“…The leaves, roots and seed are powdered together with ginger or ginger grains and applied to fractures to aid bone healing and healing of open wounds [6] and as nerve poison to cause paralysis [7]. Methanol leaveand root extracts of Pauliniapinnataare rich sources of phenolic compounds [8] while the methanol stem bark extract have been found to contain bioactive constituents which possess anti-convulsant activity [9] with a median lethal dose of 2346.42 mg/kg.…”
Section: Introductionmentioning
confidence: 99%